Retained intrauterine sutures for 6 years - Mukhit Sarsembayev; Svetlana Shikanova; Bakyt Karimova; Gulmira Mukhambetalyeva; Ibrahim A Abdelazim (Wolters Kluwer Medknow Publications, 2020)
The most common sutures used for uterine suturing during cesarean section (CS) are vicryl and/or chromic catgut. The sutures' chemistry and polymer morphology alter sutures' performance and absorption. If the sutures used during CS undergo inappropriate hydrolysis and absorption, the retained intrauterine sutures may cause intrauterine inflammations with subsequent abnormal uterine bleeding (AUB) and/or infertility. This report represents a rare case report of retained intrauterine sutures for 6 years after previous CS, which were incised and released from its attachment to the uterine wall using operative hysteroscopy. This report highlights that the retained intrauterine sutures may interfere with sperm transport and implantation and act as a foreign body with subsequent intrauterine inflammation and infertility. In addition, the report highlights the role of a hysteroscopy as the gold standard for uterine cavity assessment in women presented with AUB and/or infertility.